Artworkshop as work transition for persons with mental retardation - Rodas, Dhanna Kerina R. Bautista
This study aimed to develop an Art Workshop that would serve as a transition program to provide persons with mental retardation (PMR) career education in visual art production. The Art Workshop was developed, conducted, and documented on digital video. Informal assessment methods such as a narrative journal of daily observations, work sample analysis portfolio analysis, and expert validation were used. It was proven that PMR can brainstorm, conceptualize, and verbalize what they remember about a significant event in thier life and express their ideas into visual art. Artwork done by PMR can be used as design for the front cover of a greeting card. Cost analysis of the card shows that it can be developed into a marketable product that can generate income when sold.